2018
DOI: 10.1016/j.celrep.2018.03.126
|View full text |Cite
|
Sign up to set email alerts
|

Active Zone Scaffold Protein Ratios Tune Functional Diversity across Brain Synapses

Abstract: High-throughput electron microscopy has started to reveal synaptic connectivity maps of single circuits and whole brain regions, for example, in the Drosophila olfactory system. However, efficacy, timing, and frequency tuning of synaptic vesicle release are also highly diversified across brain synapses. These features critically depend on the nanometer-scale coupling distance between voltage-gated Ca channels (VGCCs) and the synaptic vesicle release machinery. Combining light super resolution microscopy with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
78
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 52 publications
10
78
0
Order By: Relevance
“…To further characterize the progression of striatal synaptic 1-120hαSyn aggregation, we used dSTORM, which allows detection of protein distribution at single molecule level and 20nm resolution. Although dSTORM has been successfully employed to study synaptic proteins (Bar-On et al, 2011;Bar-On et al, 2012;Bielopolski et al, 2014;Fulterer et al, 2018;Tang et al, 2016) we believe that this is the first time that dSTORM is used to analyze the progression and rescue of presynaptic αSyn pathology in vivo in brains of a PD mouse model. dSTORM confirmed a progressive aggregation of 1-120hαSyn in the MI2 mouse striatum.…”
Section: Discussionmentioning
confidence: 95%
“…To further characterize the progression of striatal synaptic 1-120hαSyn aggregation, we used dSTORM, which allows detection of protein distribution at single molecule level and 20nm resolution. Although dSTORM has been successfully employed to study synaptic proteins (Bar-On et al, 2011;Bar-On et al, 2012;Bielopolski et al, 2014;Fulterer et al, 2018;Tang et al, 2016) we believe that this is the first time that dSTORM is used to analyze the progression and rescue of presynaptic αSyn pathology in vivo in brains of a PD mouse model. dSTORM confirmed a progressive aggregation of 1-120hαSyn in the MI2 mouse striatum.…”
Section: Discussionmentioning
confidence: 95%
“…Alterations in the stoichiometry of those AZ scaffolding proteins could therefore be a general principle to determine the ratio of closely vs. loosely coupled release sites, thereby determining synaptic pV r and STP. In fact, it was recently shown that the ratio between BRP and Syd‐1 varied largely between synapse types of the Drosophila brain, in line with cell‐specific regulation of coupling distances . High BRP/Unc13A levels supported fast synaptic transmission and STD, while Syd‐1/Unc13B rich synapses were rather slow and exhibited STF .…”
Section: Perspective and Conclusionmentioning
confidence: 86%
“…In fact, it was recently shown that the ratio between BRP and Syd‐1 varied largely between synapse types of the Drosophila brain, in line with cell‐specific regulation of coupling distances . High BRP/Unc13A levels supported fast synaptic transmission and STD, while Syd‐1/Unc13B rich synapses were rather slow and exhibited STF . Syd‐1 and Liprin‐α have homologs in mammals and C. elegans .…”
Section: Perspective and Conclusionmentioning
confidence: 87%
See 2 more Smart Citations